CALCULATION OF POST-EMPLOYMENT BENEFITS WITH REGARD TO THE MULTIPLE DECREMENT TABLE AND PROJECTED UNIT CREDIT (PUC) METHOD - Ahadyat, Oktavianto
Calculation of post-employment benefits is all forms of benefits provided by an entity for services rendered by employees to the entity. Labor's law number 13 year 2003 require companies to provide post-employment benefits guarantees. The funds are known as liabilities or technical reserves which must be calculated actuarially. The aim of this research is to calculate the amount of post-employment benefits for employees of PT XYZ. Based on PSAK 24 regarding employee benefits, there are demographic assumptions and financial assumptions. The demographic assumptions consist of assumptions about mortality (mortality rate), disability rate, turnover rate (resignation rate) and normal retirement. While the financial assumptions consist of the discount rate and salary increment rate. There are several methods in actuarial calculations, one of them is the projected unit credit method from the large group of accrued benefit cost method, namely projecting aspects of the calculation. Data obtained from PT XYZ, consists of 144 employees which attach the date of birth, date of employment and salary which will be processed and analyzed before calculating. Furthermore, the amount of current service costs and present value benefit of obligation is calculated with regard to the multiple decrement table and using the projected unit credit method. This calculation takes with regard to the demographic assumptions of TMI IV, disability rate of 2%, resignation rate of 10% per year at the age of 13 to 20 years, then decreases linearly at the age of 21 years to retirement age and normal retirement age of 57 years. While the financial assumptions are the salary increase of 6% and the discount rate of 7.7269%. Based on the calculation, the current service cost as of December 31, 2019 is IDR 463,351,051,- and the present value benefit of obligation is IDR 7,568,798,977,-.